1993
DOI: 10.1007/bf02441800
|View full text |Cite
|
Sign up to set email alerts
|

Propagation in the AV node: A model based on a simplified two-dimensional structure and a bidomain tissue representation

Abstract: A model is proposed to explain mechanisms of propagation in the atrioventricular (AV) node of the heart. The model is based on a simplified two-dimensional anatomic description of the central node region and on a bidomain tissue model for the propagation. The central region is described as a three-tissue compartment model; the proximal tissue composed of ANL cells, the central tissue composed of N cells and the distal tissue composed of NH cells. The central N region is outlined as an unexcitable gap by forcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Mathematical simulations have been used to investigate important aspects of AVN activity, generally focusing on conduction phenomena such as slowed or blocked A-V conduction, or electrotonic inhibition (e.g. [Urushibara et al, 1987;Ikeda et al, 1990;LeBlanc & Dube, 1993;Liu et al, 1993;Sun et al, 1995;Meijler et al, 1996]). However, whilst such models may have simulated effectively some aspects of AVN function, either they can reproduce macroscopic AVN behavior without the incorporation of single cell activity, or valuable cellular electrophysiological information has emerged since their inception.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical simulations have been used to investigate important aspects of AVN activity, generally focusing on conduction phenomena such as slowed or blocked A-V conduction, or electrotonic inhibition (e.g. [Urushibara et al, 1987;Ikeda et al, 1990;LeBlanc & Dube, 1993;Liu et al, 1993;Sun et al, 1995;Meijler et al, 1996]). However, whilst such models may have simulated effectively some aspects of AVN function, either they can reproduce macroscopic AVN behavior without the incorporation of single cell activity, or valuable cellular electrophysiological information has emerged since their inception.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of human AVN attributed Wenckebach periodicity to a step-delay mechanism ( 30 , 31 ), and intracellular microelectrode studies on rabbit AVN indicated that the increase in AVN delay with decreasing cycle length could not be explained by decremental conduction but a step-delay located centrally in the AVN ( 32 ). Mathematical models of AVN propagation and Wenckebach behavior included step-delays localized within the node ( 33 , 34 ). These studies expressed the compelling requirement of a step-delay mechanism despite speculation about the nature of and precise location of this component of AV delay.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous cellular types composing the AVN are very heterogenous with only the midnodal cells similar to SAN pacemaker ones in terms of HCN4, L-type Cav1.2/1.3, and T-type Cav3.1/3.2 channels. In the peripheral regions, cells organize in multiple, separated bundles with few gap junction connections (specific regional repertoire of Cxs) and voltage-gated Nav1.5 channels (responsible for I Na current), characteristics that likely contribute to the AVN delay onset and maintenance [69,80,[85][86][87][88][89].…”
Section: The Embryological Development Anatomy and Physiology Of The Heart Rhythmmentioning
confidence: 99%